Excel 2013 bible - Walkenbach, John (Wiley, 2013)
Excel at Excel with the help of this bestselling spreadsheet guide. John Walkenbach's name is synonymous with excellence in computer books that decipher the complexities of Microsoft Excel. Known as "Mr. Spreadsheet," Walkenbach shows you how to maximize the power of Excel 2013 while bringing you up to speed on the latest features. This perennial bestseller is fully updated to cover all the new features of Excel 2013, including how to navigate the user interface, take advantage of various file formats, master formulas, analyze data with PivotTables, and more. Whether you're an Excel beginner who is looking to get more savvy or an advanced user looking to become a power user, this latest edition provides you with comprehensive coverage as well as helpful tips, tricks, and techniques that you won't find anywhere else. Shares the invaluable insight of Excel guru and bestselling author "Mr. Spreadsheet" John Walkenbach as he guides you through every aspect of Excel 2013. Provides essential coverage of all the newest features of Excel 2013 .Presents material in a clear, concise, logical format that is ideal for all levels of Excel experience. Features a website that includes downloadable templates and worksheets from the book. Chart your path to fantastic formulas and stellar spreadsheets with iExcel 2013 Bible.